Natural antioxidants that act against Alzheimer’s disease through modulation of the NRF2 pathway: a focus on their molecular mechanisms of action - Sidiropoulou, Grammatiki Alexandra; Metaxas, Athanasios; Kourti, Malamati (Frontiers in Endocrinology, 2023)
Characterized by a complex pathophysiology that includes the intraneuronal formation of neurofibrillary tangles and the extracellular deposition of β-amyloid plaques, Alzheimer's disease (AD) is a terminal neurodegenerative disease that causes dementia in older adults. Oxidative stress in the brain is considered as one of the contributing factors to the pathogenesis of AD, and thus, antioxidants have attracted much interest as potential therapeutic agents against the disorder. Natural antioxidants are typically characterized by low acute and chronic toxicity, which facilitates their potential therapeutic application. One important molecular target for the beneficial effects of natural antioxidants is the nuclear factor erythroid-derived 2-related factor 2 (NFE2L2/NRF2). NRF2 is a key transcription factor that orchestrates the cellular antioxidant response through regulating the expression of oxidative stress-related genes harboring the antioxidant response element (ARE) in their promoters. Indeed, in the case of excessive oxidative damage, NRF2 migrates to the nucleus and binds to ARE, activating the transcription of antioxidant protector genes. There is increasing evidence that NRF2 is implicated in AD pathology through dysfunction and altered localization, which renders it as a potential therapeutic target for AD. Thus, this review summarizes the most recent (2018-2023) advances on the NRF2-modulating activity of natural antioxidants observed in vitro and in AD animal models. This information will help elucidate the molecular mechanisms governing the antioxidant activity of such phytochemicals to highlight their therapeutic potential against common neurodegenerative diseases, such as AD.